Sistem Penjawab Otomatis Berbasis Chatbot Untuk Unit Pengelola Pembelajaran Daring Universitas Telkom - Abdul Karim, Iim; Noor Prawita, Fathah (eProceedings of Applied Science, 2023)
Abstract— In the era of digital technology, information is very important in this era. Almost all fields in this world require information. This includes the information needs of certain service units at a university. The application of chatbot artificial intelligence in the information field will make it easier for humans. This is an opportunity for the online learning service unit at Telkom University, namely CeLOE to make it easier to provide information to CeLOE users by implementing a chatbot, because so far CeLOE users who need information have to contact customer service manually. customer service often asks repeated questions. In this final project, a chatbot will be implemented to make it easier for users to get information efficiently by utilizing a chatbot platform. The test results in this final project are chatbots are able to overcome the problem of customer service CeLOE and make it easy for users to get information.Keywords— chatbot, customer service, information, artificial intelligence